2015
DOI: 10.1186/s13023-015-0243-8
|View full text |Cite
|
Sign up to set email alerts
|

The genotypic and phenotypic spectrum of PIGA deficiency

Abstract: BackgroundPhosphatidylinositol glycan biosynthesis class A protein (PIGA) is one of the enzymes involved in the biosynthesis of glycosylphosphatidylinositol (GPI) anchor proteins, which function as enzymes, adhesion molecules, complement regulators and co-receptors in signal transduction pathways. Until recently, only somatic PIGA mutations had been reported in patients with paroxysmal nocturnal hemoglobinuria (PNH), while germline mutations had not been observed, and were suspected to result in lethality. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(106 citation statements)
references
References 44 publications
(91 reference statements)
7
99
0
Order By: Relevance
“…Other phenotypes such as polyhydramnios, elevated alkaline phosphatase (ALP), cardiac anomalies, dental problems, visual impairment and deafness were also seen in these patients although less frequently, and some phenotypes were reported only once such as nephrocalcinosis, short fingers or hands, and skeletal anomalies. These widespread clinical features are consistent with the findings that the PIGA protein is expressed in a wide variety of tissues including brain, liver, heart and blood cells . In the 21 patients reported, about half of them died in which the cause of death was mainly due to liver failure and respiration pneumonia.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Other phenotypes such as polyhydramnios, elevated alkaline phosphatase (ALP), cardiac anomalies, dental problems, visual impairment and deafness were also seen in these patients although less frequently, and some phenotypes were reported only once such as nephrocalcinosis, short fingers or hands, and skeletal anomalies. These widespread clinical features are consistent with the findings that the PIGA protein is expressed in a wide variety of tissues including brain, liver, heart and blood cells . In the 21 patients reported, about half of them died in which the cause of death was mainly due to liver failure and respiration pneumonia.…”
Section: Resultssupporting
confidence: 87%
“…In the 21 patients reported, about half of them died in which the cause of death was mainly due to liver failure and respiration pneumonia. Some patients also have evidence of mitochondrial dysfunction, although the mechanism for this phenomenon is not known . Studies in induced pluripotent stem cells showed decreased proliferation, abnormal synapse formation, membrane depolarization and an increased susceptibility to complement‐mediated cytotoxicity …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cells defective in early steps in the GPI biosynthetic pathway, GPI transamidase action to preproproteins is less effi cient and preproproteins are degraded by ER-associated degradation. Indeed, hyperphosphatasia does not occur, or occurs only mildly, in PIGA -, PIGQ -, and PIGL -defi ciencies (119)(120)(121). Balance between degradation and secretion due to cleavage by GPI transamidase seems to be affected by other unknown factors, such as genetic backgrounds, because highly elevated hyperphosphatasia associated with PIGL -defi ciency was recently reported ( 122 ).…”
Section: Defi Ciency In Pgap1mentioning
confidence: 99%
“…The clinical characteristics of our case were very similar to those reported previously by Kato et al 11 The phenotype of our case could be classified into severe PIGA deficiency in cluding refractory epileptiform discharges with a burstsuppression pattern on EEG, dysmorphic features and anomalies of other organs. 12 Our case showed no anemia or paroxysmal nocturnal hemoglobinuria that is caused by somatic PIGA mutations. In contrast to other cases with mutations in PIGA, our case exhibited congenital malformation with omphalocele.…”
Section: Introductionmentioning
confidence: 97%